Markets and market liberalization ethnographic reflections - Cynthia Werner; Dannhaeuser, Norbert, 1943-; Werner, Cynthia Ann, 1967- (Emerald, 2006)
The general theme of Volume 24 is the impact of, and reaction to, the spread of market systems and market liberalization by local communities. Part I examines cases in which migration has opened new market and entrepreneurial opportunities to local populations. Part II contains cases that describe ethnographically the impacts the oil industry market has had on towns of Louisiana's Gulf coast. The essays of Part III concern themselves with community repercussions that recent neoliberal market policies have had, while Part IV contains papers that analyse the process in which values of products and services are defined economically, culturally and politically in the context of developing markets and commoditization. This book focuses on market systems and market liberalization in local communities. Specific topics addressed include the oil industry and the gulf coast, negotiating values in the market, and many more. The international case examples provide a global perspective.
Keywords: Business & Economics -- Management Science.; Business & Economics -- Economics -- General.; Economics.; Physical anthropology & ethnography.; Economic anthropology.; Economic development -- Cross-cultural studies.; Consumption (Economics) -- Cross-cultural studies.; Labor -- Social aspects.; elektronické knihy; electronic books